Perspectives and experiences of physiotherapists and general practitioners in the use of the STarT Back Tool: a review and meta-synthesis - Nicola Saywell; Georgia Agnew; Freya Try; Julia Hill (CSIRO Publishing, 2022)
Introduction The STarT Back Tool (SBT) is used to triage people with acute low back pain (LBP) into treatment groups, matched to their risk of chronicity. It was developed in the UK where it has been shown to improve clinical outcomes, patient satisfaction, and reduce time off work. Successful implementation of the SBT outside the UK is dependent on health practitioner's attitudes and the healthcare system in which they work. Gaining health practitioners' perspectives on the SBT is an important step in implementation. Methods A computerised search of qualitative literature was conducted across seven databases in March 2021 using keywords to identify studies investigating the perspectives of physiotherapists and general practitioners on the use of the SBT in primary health care. Study quality was assessed using the Critical Appraisal Skills Programme (CASP) tool. Data were coded and analysed using reflexive thematic analysis. Results Eight articles met inclusion criteria and included the views of 76 physiotherapists and 65 general practitioners, working in primary health care in four countries. Three themes were created from the data: 'Making it work', identifies factors that influence implementation and continued use of the SBT. The second 'will I do it?', captured potential consequences of adopting the SBT, and the third, 'it's all about the patient' emphasised how the SBT may  affect patients. Discussion Physiotherapists and general practitioners found using the SBT frequently enhanced practice. General practitioners expressed concerns about time constraints and the SBT's potential to undermine clinical experience. Findings from this study will inform modifications to contextualise the tool to each healthcare environment.